A taxonomic revision of the small Cape genus Steirodiscus (Asteraceae: Senecioneae) - Manning, J.C.; Goldblatt , Peter; Joubert, L. (African Biodiversity & Conservation, 2013)
The genus Steirodiscus Less. is revised, with full descriptions, nomenclature, illustrations and distribution data. Five species are recognised in two sections: sect. Steirodiscus with free involucral bracts and sect. Psilothonna with bracts connate into a smooth cup. S. linearilobus DC. is established as an earlier name for S. schlechteri Bolus, which is relegated to synonomy.